Fiber break location technique utilizing stimulated Brillouin scattering effects in optical fiber - Bakar, A.A.A.; Al-Mansoori, M.H.; Mahdi, Mohd Adzir; Zainal Abidin, Mohd Shahnan; Mohd Azau, M.A. (Wiley - VCH Verlag GmbH & CO. KGaA, 2009)
A new technique of fiber break detection system in optical communication networks is proposed and experimentally demonstrated in this paper. This technique is based-on continuous wave light source rather than pulsed source that is commonly deployed in existing techniques. The nonlinear effect of stimulated Brillouin scattering is manipulated to locate the fiber-break position in optical communication networks. This technique enables the utilization of a less-sensitive photodetector to detect the Brillouin Stokes line since its intensity increases with the fiber length in the detectable region. The fiber break location can be determined with accuracy of more than 98% for fiber length less than 50 km using this technique.